Baseline risk markers and visit-to-visit variability in relation to kidney outcomes – A post-hoc analysis of the PERL study. (November 2022) - Rotbain Curovic, Viktor; Roy, Neil; Hansen, Tine W.; Luiza Caramori, M.; Cherney, David Z.; De Boer, Ian H.; Emanuele, Mary Ann; Hirsch, Irl B.; Lingvay, Ildiko; Mcgill, Janet B.; Polsky, Sarit; Pop-Busui, Rodica; et al.
Abstract: Background: Baseline risk variables and visit-to-visit variability (VV) of systolic blood pressure (SBP), HbA1c, serum creatinine, and uric acid (UA) are potential risk markers of kidney function decline in type 1 diabetes. Methods: Post-hoc analysis of a double-blind randomized placebo-controlled clinical trial investigating allopurinol's effect on iohexol-derived glomerular filtration rate (iGFR) in type 1 diabetes with elevated UA. Primary outcome was iGFR change over three years. Linear regression with backwards selection of baseline clinical variables was performed to identify an optimized model forecasting iGFR change. Furthermore, VVs of SBP, HbA1c, serum creatinine, and UA were calculated using measurements from the run-in period; thereafter assessed by linear regression, with iGFR change as the dependent variable. Results: 404 participants were included in the primary analyses. In the optimized baseline variable model, higher HbA1c, SBP, iGFR, albuminuria, and heart rate, and mineralocorticoid receptor antagonist prescription were associated with greater iGFR decline. Higher VV of SBP was associated with greater iGFR decline (adjusted β (ml/min/1.73 m 2 /50 % increase): −0.79, p = 0.01). Conclusions: We identified several risk markers for faster iGFR decline in a high-risk population with type 1 diabetes. While further research is needed, our results indicate possible new and clinically feasible measures to risk stratify for DKD in type 1 diabetes.